2017
DOI: 10.1007/s11258-017-0718-x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in and adaptive plasticity of flower size and drought-coping traits

Abstract: Although phenotypic plasticity of morphological and physiological traits in response to drought could be adaptive, there have been relatively few tests of plasticity variation or of adaptive plasticity in drought-coping traits across populations with different moisture availabilities. We measured floral size, vegetative size, and physiological traits in four field populations of Leptosiphon androsaceus (Polemoniaceae) that were distributed across a rainfall gradient in California, USA. Measurements were made o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
(118 reference statements)
0
15
1
Order By: Relevance
“…Water loss from flowers may also influence flower size. Work with L. bicolor and the closely related L. androsaceus has demonstrated that flowers of Leptosiphon lose substantial amounts of water, and plants may produce smaller flowers in drier locations or conditions in order to limit that loss (Lambrecht, 2013; Lambrecht, Morrow, & Hussey, 2017). Floral water loss of Leptosiphon and other plant species has been shown to affect leaf physiology and can lead to reduced gas exchange, particularly in dry conditions (Dudley, Arroyo, & Fernandez‐Murillo, 2018; Galen, Sherry, & Carroll, 1999; Lambrecht, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Water loss from flowers may also influence flower size. Work with L. bicolor and the closely related L. androsaceus has demonstrated that flowers of Leptosiphon lose substantial amounts of water, and plants may produce smaller flowers in drier locations or conditions in order to limit that loss (Lambrecht, 2013; Lambrecht, Morrow, & Hussey, 2017). Floral water loss of Leptosiphon and other plant species has been shown to affect leaf physiology and can lead to reduced gas exchange, particularly in dry conditions (Dudley, Arroyo, & Fernandez‐Murillo, 2018; Galen, Sherry, & Carroll, 1999; Lambrecht, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Flower size reduction was previously reported in response to drought. Carroll et al (2001) observed a reduction of 33% in flower size after 12 days of drought for Epilobium angustifolium, and Lambrecht et al (2017) reported a decrease in flower size of Leptosiphon androsaceus in response to dry years. The high water costs of flowering influence flower morphology (De la Barrera & Nobel, 2004).…”
Section: Do Temperature and Water Stress Interact With Their Effectmentioning
confidence: 99%
“…We observed that B. officinalis decreased E i and g s under water stress. A decrease in E i is a common response to water stress; plants close their stomata to limit water loss (Lambrecht, Morrow, & Hussey, 2017;Qaderi et al, 2012). Decreasing g s usually reduces plant photosynthesis (Adejare & Umebese, 2007;Khan et al, 2010).…”
Section: Do Temperature and Water Stress Interact With Their Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Such responses are not limited to vegetative traits but can also be present in floral traits. For example, a decrease in flower size, in the number of flowers and/or in floral height under drought conditions can reduce transpirational water loss through flowers ( Feild et al, 2009 ; Teixido and Valladares, 2014 ; Lambrecht et al, 2017 ) and can decrease water consumption for flower maintenance ( Galen et al, 1999 ). However, these changes are often species-specific ( Burkle and Runyon, 2016 ; Descamps et al, 2018 , 2020 ; Glenny et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%